Local administrative units and their divisions: Analytical study - Vian Hassan Abdullah; Rawiz Ahmed Jamil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The presence of local administrative units is necessitated by geographical necessities, population density, and the provision of public needs and services to citizens. On its basis, the state is divided into local or regional administrative units, each of which enjoys a public moral personality because it exercises its functions in accordance with public law as the holder of authority and sovereignty. The local administrative units exist in the state, regardless of whether the administrative system used in it is central or decentralized each administrative unit is headed by an administrative head who exercises his duties and competencies within the scope of his administrative unit and within the legal limits set for him. The head of the administrative unit is considered the chief executive and administrative head of his administrative unit.